PERAN GURU AGAMA KATOLIK DALAM PEMBINAAN IMAN SISWA KATOLIK SEKOLAH MENENGAH PERTAMA NEGERI DI KOTA MADIUN - Pratiwi, S.S Sam’hita Ayu; Permana, Natalis Sukma (CREDENDUM: Jurnal Pendidikan Agama, 2021)
A Catholic religious teacher has carried out his/her duties in public schools not only as an educator, but also as a faith companion of the students. However, the Catholic students are still experiencing particular obstacles related to the Catholic faith formation in public school. This is because of the Catholic students in public schools perceived as a minority group, and therefore getting lesser attention, especially in terms of both Catholic religious learning and faith building activities in schools. The problem studied in the research is how a Catholic religious teacher can carry out his/her role as a faith companion of the students to effectively build up the faith of Catholic students as a minority group in public schools. This study applies a qualitative research method, and research data was collected using a depth interview technique. The research informants were Catholic religious teachers who have taught at public schools for years. The results of the study indicated that Catholic religious teachers have fully understood their role as faith companions of the Catholic students in public schools. The role of Catholic religious teachers in public schools is to accompany the faith of Catholic students through faith-building activity aimed to make the faith of the students being grown and matured.